(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Arfarita N, Nuraini Y, Rinady MVP, Noerhayati E, Prayogo C. 2024. The impact of different management on pine-based agroforestry system and litter accumulation on the population and activity of cellulolytic bacteria. Biodiversitas 25: 924-936. Agroforestry leads to the accumulation of organic matter, and the environmental conditions, litter quality, and decomposing organisms influence the rate at which litter decomposes. Litter decomposition in agroforestry systems is slow due to the high lignin and phenolic substances content, low light intensity, and high humidity under the canopy’s shading condition. Therefore, a study was carried out to address this issue to isolate cellulolytic bacteria capable of breaking down plant litter using a qualitative cellulase activity testing method. The complete randomized block design and Tukey’s test were used to determine the treatment’s significance. Six agroforestry systems were examined: pine-coffee, pine-banana, pine-cardamom, pine-cardamom, mixed garden, and citrus. The PK (Pine-Coffee) plot had the highest canopy cover, litter density, and cellulolytic bacteria. The study identified three cellulolytic bacteria isolates (PK1, PK13, and PK10) from the 50 isolated bacteria of PK plot, producing the largest clear zones on CMC media. These identified isolates belonging to the Bacillus genus were Gram-positive bacteria with rod-shaped cells. The different types of litter in agroforestry systems affect the content of lignin, polyphenols, cellulose, and C/N ratios, which can influence the abundance of cellulolytic bacteria and their potential cellulase activity.